The trend in female labour force participation: what can be expected for the future? - Rob Euwals; Marike Knoef; Daniel van Vuuren (Institute for the Study of Labor (IZA), 2007)
During the 1980s and 1990s, the Netherlands experienced a strong increase in the labour force participation of women. This study investigates the increase of participation over the successive generations of women, and produces an educated guess for future participation. For this purpose, we estimate a binary age-period-cohort model for the generations born between 1925 and 1986, using data from the Dutch Labour Force Survey 1992-2004. The results indicate that the increasing level of education, the diminishing negative effect of children, and unobserved cohort effects have played an important role. According to our estimates, the increase in unobserved cohort effects has stopped since the generation born in 1955. This result is in line with results of studies on social norms and attitudes towards the combination of female employment and family responsibilities, which show a similar pattern over the successive generations. We observe that future participation growth importantly depends on the evolvement of attitudes towards the combination of paid work and children. We have therefore constructed two alternative future scenarios, the first with constant norms with respect to this factor, and the second with a further evolvement. It is estimated that the remaining growth will compensate for about one third of the structural fiscal deficit caused by population ageing in the Netherlands.
Keywords: J11; 330; Female labour force participation; age-period-cohort-analysis; future development; Frauenerwerbstätigkeit; Arbeitsangebot; Generationenbeziehungen; Kohortenanalyse; Niederlande